What are the Project Management Practices in the Digital Games Industry? A Survey Study - Lucas Pieva; Raquel Pillat; João Batista Mossmann; Maicon Bernardino (Journal on Interactive Systems)
Background: The Brazilian digital games industry has been expanding rapidly, requiring effective Project Management (PM) practices to ensure success across cost, time, and scope dimensions. Purpose: This study investigates the PM  practices, artifacts, and systems adopted by game studios and independent developers in Brazil, aiming to provide an empirical reference for researchers and practitioners. Methods: Using the Linaker survey methodology, we collected responses from 41 professionals across 21 studios, addressing four key research questions related to PM approaches, artifacts, and tools. Results: The findings reveal Scrum and Kanban as the most widely used methodologies, with artifacts such as the Game Design Document (GDD), prototypes, and Kanban boards frequently supporting project activities. Tools such as Trello, Miro, and ClickUp dominate the usage, but the lack of a standardized PM system highlights significant variability between studios. Despite the diversity, agile methods are preferred for their adaptability and alignment with industry demands. Conclusion: The study concludes that while Brazilian studios exhibit good PM practices, there are still gaps in the integration of academic insight with practical applications. The results provide valuable insights for the development of customized PM solutions for the digital games industry, emphasizing the need for further research to address scalability and complexity in larger projects.